The Correlation between the CT Liver Volume and the Actual Weight of the Resected Cirrhotic Liver in Transplantation Patients - Kulyada Eurboonyanun; Chalerm Eurboonyanun; Julaluck Promsorn; Jiranthanin Phaorod; Tharatip Srisuk; Nittaya Chamadol; Mukesh Harisinghani (Journal of Health Science and Medical Research (JHSMR), 2022)
Objective: Volumetric assessment with computed tomography (CT), known as CT volumetry, is the preferred method for estimating future liver remnant. However, the data regarding the usage of CT volumetry to estimate future liver remnant of the diseased liver is still lacking. This study was designed to evaluate the correlation between the liver volume, calculated by CT, and the actual weight of the resected liver in patients who underwent orthotopic liver transplantation. Material and Methods: A total of 32 patients having underwent liver transplantation; from March 2009 to June 2015, were included. A radiologist retrospectively reviewed the pre-operative CT and performed the volume measurement. Statistical analysis was performed to determine the relationship between the estimated liver volume and the actual liver weight. Results: The estimated liver volume was significantly different among the cirrhosis of different etiology (p-value=0.001 for the total liver volume and p-value=0.003 for the functional liver volume). Compared with the total liver volume, the functional liver volume had a stronger correlation with the actual weight of the resected liver (r=0.955 vs. r=0.786). The following formula can be used to accurately estimate the expected weight of the resected liver (expected liver weight: ELW), based on the estimated functional liver volume (FLV) derived by CT volumetry: ELW=489.531+(0.618*FLV). The R-squared for this regression model was 0.914. Conclusion: CT volumetry is reliable and accurate in predicting the actual amount of the resected liver parenchyma in cirrhotic patients.